Evaluation of ocular psoriasis with meibography - Funda Kemeriz; Burcu Tugrul; Erdogan Yasar (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background: Previous studies has shown that dry eye test abnormalities, meibomian gland dysfunction (MGD), may occur in psoriasis. Objectives: The authors aimed to evaluate the dry eye disease (DED), MGD, in psoriasis patients with meibography which is a current, objective, noninvasive method for patients with meibomian gland diseases, to investigate the relationship between disease severity and ocular involvement. Methods: This study included 50 participants with psoriasis and 50 healthy individuals. All subjects were examined by the same dermatologist and referred for ophthalmological examination including meibomian gland obstruction, lid margin alterations assessment, ocular surface disease index assessment, tear film break-up time test, Schirmer test, corneal conjunctival fluorescein staining assessment. Additionally, upper and lower lids were evaluated for meibomian gland loss with meibography. Results: MGD (28%), meibomian gland loss (MGL) (29.5%), upper meiboscore (0.61 ± 0.81), lower meiboscore (0.46 ± 0.61), DED (22%) were significantly higher in the psoriasis group compared with the control group (p = 0.008, p < 0.001, p = 0.027, p = 0.041, p = 0.044, respectively). There was a significant relationship between MGD and psoriasis area severity index (PASI) (p = 0.015, Odds Ratio = 1.211). There was a significant positive relationship between MGL with PASI (p < 0.001, r = 608) and psoriasis duration (p < 0.001, r = 0.547). Study limitations: Smaller study group and inability to detect quality changes of meibum with meibography were limitations of the study. Conclusions: Psoriasis may affect the meibomian gland morphology, may cause structural changes in meibomian glands, and as a result of these may cause MGD and DED. Therefore, ophthalmologists and dermatologists should be aware of this situation and co-evaluate the patients in this respect.